Բանի եւ հացի համընկալումը. Դանիել Վարուժան - Թադեւոս Տոնոյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В нескольких статьях посвященных свойствам языкового мышления автор этой статьи выдвигал идею синонимов в языковом мышлении. In this article, as in previous publications, author proposes the idea of synonymy in lingual-thinking which is different from linguistic synonymy.
Keywords: Literature; Criticism